PENATAAN PERMUKIMAN KUMUH DI DESA NANAS SIAM KECAMATAN MEDANG DERAS KABUPATEN BATUBARA PROPINSI SUMATERA UTARA - Suhaila Husna Samosir (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2018)
Indonesia's urban slum neighborhood is a very complex problem, including problems related to poverty, low levels of community education, gaps and indiscriminately to the environment as well as the capacity of city / district government institutions in regulating, organizing spatial planning and resources owned. One of them in the Village Nanas Siam Kecamatamn Medang Deras Batubara District. Problems that occur in the field was quite complex. Many of the things that affect the emergence and the process of the region into a slum with a variety of characteristics of the problem. From the results of research can be seen that the condition of slum neighborhoods in the village of Nanas Siam Kecamatamn Medang Deras Batubaram regency is very bad. This can be seen from the density of buildings in the area that are not in accordance with the spatial planning that may cause flood and fire hazard. In addition, the low level of environmental hygiene and hygiene facilities and infrastructure in the slums. Keywords: Structuring, Slum Areas